Prevalence and Anatomical Distribution of Bone Stress Injuries in the Elite Para Athlete. (November 2019) - Tenforde, Adam S.; Brook, Emily M.; Broad, Elizabeth; Matzkin, Elizabeth G.; Yang, Heidi Y.; Collins, Jamie E.; Braun, Peter W.; Blauwet, Cheri A.
Abstract : Abstract: Bone stress injury is a common overuse injury in athletes. Risk factors for bone stress injury in athletes include the female athlete triad (triad); this has not been evaluated in para athletes. The aim of this study was to identify risk factors, prevalence, and anatomical distribution of bone stress injury in para athletes. A cross-sectional online survey on health characteristics and previous fractures including bone stress injury was completed by para athletes training for the 2016 or 2018 Paralympic Games. Two hundred sixty para athletes completed the survey (659 invited, response rate = 40%). Half reported previous fracture, and bone stress injury was reported in 9.2% of all athletes. Twenty-four athletes (11 men and 13 women) sustained one or more bone stress injury, including 13 athletes with two bone stress injuries. No risk factors of the triad, disability type, or duration of disability were associated with bone stress injury. Injuries were most common in the metatarsals ( n = 8) and hand/wrist ( n = 7). In an elite para athlete population, locations for bone stress injury included both the upper and lower limbs. Clinically, para athletes presenting with pain localized to bone require further workup to evaluate for bone stress injury particularly for pain in both upper and lower limbs. Further research is required to identify risk factors for bone stress injury in para athletes.